Krisis Keuangan 2008 dan Dampaknya Terhadap Kualitas Pembangunan Manusia di Negara Konferensi Islam - Hilal Fathurrahman; Mohammad Nur Rianto Al Arif (Faculty of Economics and Business, 2022)
This study aims to analyze effect that occurs between Finansial Crisis 2008 on Human Development Index in OIC and Non-OIC countries for the period 2006-2021. This study used secondary data with stratified sampling method. Methods of data analysis using Difference in Difference (DiD). The results of processing with DiD show that only Balance of Payment is significant and positively affects the human development index in OIC and Non-OIC countries, while the variable rate of inflation, economic growth, population and unemployment rate are significant but negatively on the human development index. The results also showed that there was no effect between conditon pre and post crisis on human development index for the period 2006-2021.